Mass Mimicking a Posterior Mediastinal Tumor Caused by the Extramedullary Hematopoiesis in Beta Thalassemia Major : a Rare Case Report - Nurzuwita Hasibuan; Mulia Wati; Khairida Riany; Ghamal Arif Hanafiah; Amna Wahyuni (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2026)
Extramedullary hematopoiesis (EMH) refers to the production of blood cells occurring outside the bone marrow. This phenomenon is uncommon in individuals with moderate to severe β-thalassemia. The liver, spleen, and lymph nodes are the most frequent sites of EMH, while more unusual locations include the kidneys, intrathoracic cavity, skin, and central nervous system. Case Illustration: A 59-year-old man presented with complaints of shortness of breath, cough, and fatigue for the past one month. There was no previous history of blood disorders. Chest radiography revealed a lobulated mass in the posterior mediastinum. Contrast-enhanced thoracic CT scan demonstrated a lobulated mass of heterogeneous density containing blood components and calcifications, located between vertebrae T6 and T12. Laboratory findings showed microcytic hypochromic anemia (hemoglobin 6.2 g/dL, mean corpuscular volume 77 fL, mean corpuscular hemoglobin 26 g/dL) with reticulocyte count of 2.9%. Hemoglobin electrophoresis confirmed the diagnosis of β-thalassemia major. Discussion: Extramedullary hematopoiesis in the posterior mediastinum is rare and is often clinically silent, as observed in this case, and frequently discovered incidentally. On thoracic CT scans, EMH typically appears as unilateral or bilateral, well-circumscribed paravertebral masses located between vertebrae T6 and T12, with soft tissue density. These masses may contain adipose tissue and are occasionally associated with calcification. Conclusion: Extramedullary hematopoiesis is rare in moderate to severe β-thalassemia and may involve any site in the body. Posterior mediastinal involvement is uncommon and usually asymptomatic. Chest CT scan plays a crucial role in the diagnosis of mediastinal EMH.